Comportamiento de la escorrentía superficial en las vertientes de una cuenca hidrográfica en el ecosistema dehesa. Cuenca del Guadalperalón (provincia de Cáceres) - Ceballos, Antonio; Schnabel, Susanne (Geographicalia, 2017)
In a small catchment under the dehesa land use system overland flow production on slopes is investigated. The obtained results show that the determination of the threshold value for the generation of runoff is complex. Total precipitation and rnaximun intensity in 10 minutes are the principal factors that explain the production and generation of slope runoff.
Keywords: dehesa ecosystem; overland flow; slopes